A Single Case Study of Transpersonal Dynamics among a Working University Student Following the Death of His Father - Najwa Aurellia Putri; Sabti Riguna Hidayah; Fatimah Azzakiyah; Aida Ad’ha; Birgita Intan Sherlyna (The Future of Education Journal, 2026)
This study aims to explore the dynamics of transpersonal experiences among a working university student following the death of his father, encompassing alcohol consumption as a form of emotional escape, religious disengagement, and recovery through non-coercive spiritual companionship. The study employed a qualitative approach using a single-case study design. The participant was "R," a 26-year-old male university student working full-time in the logistics sector who experienced the sudden loss of his father during the COVID-19 pandemic. Data were collected through three sessions of semi-structured in-depth interviews, non-participant observation, and document analysis. The data were analyzed using Braun and Clarke’s reflexive thematic analysis. The findings revealed that the participant perceived his father's death as a profound loss of life direction and purpose rather than as divine punishment. Alcohol functioned as a form of counterfeit transcendence, providing temporary relief and emotional escape. The participant experienced religious disengagement, characterized by a substantial decline in religious practices and, at one point, self-identification as an agnostic. His belief that alcohol consumption invalidated worship for forty days further reinforced the cycle of spiritual withdrawal. Recovery emerged through the presence of significant others who gently "guided him back to the right path" without coercion, representing a form of non-coercive spiritual companionship that gradually facilitated his return to his spiritual identity. Identified risk factors included multirole stress, traumatic grief, and maladaptive coping, whereas protective factors comprised spiritual companionship, non-coercive presence, and meaning reconstruction. This study contributes to the advancement of transpersonal psychology by enriching the understanding of the disintegration of transcendent functioning and proposing a novel conceptual framework of transpersonal recovery through non-coercive spiritual companionship.